IL-17 Induces Autophagy Dysfunction to Promote Inflammatory Cell Death and Fibrosis in Keloid Fibroblasts via the STAT3 and HIF-1α Dependent Signaling Pathways - Lee, Seon-Yeong; Lee, A Ram; Choi, Jeong Won; Lee, Chae Rim; Cho, Keun-Hyung; Lee, Jung Ho; Cho, Mi-La (Frontiers in Immunology, 2022)
Keloid is an abnormal fibrotic disease after cutaneous injury characterized by exaggerated scar tissue formation, which often extends beyond the boundaries of the original wound. Although chronic inflammation is known to be associated with the excessive inflammation in keloid tissue, there are few studies on the role of autophagy in the pathogenesis of keloid. In this study, we evaluated the pattern of autophagy in keloid fibroblasts (KF) and normal fibroblasts (NF). Expression of HIF-1α, STAT3 and autophagic flux markers were evaluated in KF and NF. Defective autophagy caused by IL-17 was evaluated, and the relationship between defective autophagy and necroptosis was also examined. The expression of IL-17, HIF-1α and STAT3 was significantly increased in keloid tissue, and autophagosome-to autophagolysosome conversion was defective in KF. IL-17 treatment significantly elevated the expression of STAT3 and HIF-1α in NF and caused defective autophagy, which was reversed by HIF-1α inhibitor. In addition, the defective autophagy was associated with the increased necroptosis and fibrosis. In keloid tissue, the elevated necroptosis marker was confirmed, and with the HIF-1α inhibitor, the defective autophagy, necroptosis and fibrosis was decreased in KF. In conclusion, autophagy was defective in keloid tissue, which was associated with increased necroptosis and fibrosis. The IL-17-STAT3-HIF-1α axis was involved in defective autophagy in KF, and this suggests that targeting the axis could alleviate chronic inflammation in keloid disease.